Agile Education: Luisa Collina on the evolution of Design Schools - Valentina Auricchio (Agathón)
Job positions are changing, students are changing, together with their needs and dreams, technologies evolve and new forms of collaboration are arising, but what can universities do to promptly react to global processes? Within a dialogue with Luisa Collina, retracing the main stages that characterized the birth and evolution of design schools in Italy, a future vision emerges. A vision that preserves and emphasizes the glorious history of the past while taking into account its own DNA, characterized by a critical and strategic nature, in continuous dialogue with industry, but also with the arts, crafts and humanistic disciplines.